2012
DOI: 10.2147/ijn.s28978
|View full text |Cite
|
Sign up to set email alerts
|

Degradable biocomposite of nano calcium- deficient hydroxyapatite-multi(amino acid) copolymer

Abstract: Background and methods:A nano calcium-deficient hydroxyapatite (n-CDHA)-multi(amino acid) copolymer (MAC) composite bone substitute biomaterial was prepared using an in situ polymerization method. The composition, structure, and compressive strength of the composite was characterized, and the in vitro degradability in phosphate-buffered solution and preliminary cell responses to the composite were investigated. Results: The composite comprised n-CDHA and an amide linkage copolymer. The compressive strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…In previous research, 9 it was found that the compressive strength of this n-CDHA-MAC composite was about 127 MPa, which is similar to that of natural cortical bones of humans. 16 In our study, the n-CDHA-MAC composites were processed into a tubular shape, thus preserving the continuity of the diaphysis for the repair of large diaphyseal bone defects.…”
Section: -13supporting
confidence: 63%
See 4 more Smart Citations
“…In previous research, 9 it was found that the compressive strength of this n-CDHA-MAC composite was about 127 MPa, which is similar to that of natural cortical bones of humans. 16 In our study, the n-CDHA-MAC composites were processed into a tubular shape, thus preserving the continuity of the diaphysis for the repair of large diaphyseal bone defects.…”
Section: -13supporting
confidence: 63%
“…9,19 The femur length and thickness were measured in six fresh femurs of 2-year-old goats (of either sex and either side of femur) to make the 30 mm-segment bone defects and measure the diameter of proximal and distal ends. Femur length from the intertrochanteric fossa to the midpoint of the medial and lateral condyle were measured as the standard length.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations